Perubahan Pemanfaatan Ruang Sebelum dan Sesudah Penetapan Kawasan Perkotaan SARBAGITA Di Kecamatan Kuta Utara - I Putu Windhu Sanjaya; Agam Marsoyo (Universitas Muhammadiyah Mataram, 2019)
Kuta Utara district is a suburb of Denpasar City which is currently experiencing rapid development, especially in its use of space. Since 2011, North Kuta District has been designated as part of the development area of the Sarbagita urban area which is a national strategic area. This study is related to changes in spatial use to describe changes in spatial use that occurred before and after the determination of the Sarbagita urban area. The analysis carried out was overlaying a map of land use change in 2003, 2011 and 2017. The results of this study indicate a rapid change in spatial use from the period 2011 to 2017 indicated by changes in land not built into built-up land.